Drawing Fields: Prototyping public space with semi-autonomous robots. (December 2021) - Herrmann, Erik W; Bigham, Ashley
This paper is a concise report of Drawing Fields, a temporary performance venue on the campus of Ragdale, a nonprofit artists' community just north of Chicago. Drawing Fields utilizes GPS-controlled field marking robots to draw site-specific, building-scale drawings on the Ragdale campus. Each drawing in the series explores a different theme with Drawing Fields 1 probing robotic kinetics, Drawing Fields 2 delineating socially-distanced zones for a scattered audience, and Drawing Fields 3 saturating the campus with colorful patterns. The report discusses the project implementation and includes a brief discussion of the project's cultural, ecological and technological resonances.